1999
DOI: 10.21236/ada382201
|View full text |Cite
|
Sign up to set email alerts
|

Career Plans and Military Propensity of Young Women: Interviews with 1997 Youth Attitude Tracking Study Respondents

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our interviews with individuals in the DEP conducted in the first phase of the project (Sticha et al, 1997) indicated that some did not have definite plans for their lives before they enlisted. This result was similar to a decision making style that was identified by in depth follow-up interviews conducted with YATS respondents (Berkowitz, Perry, Giambo, Wilson, & Lehnus, 1997). These results suggested that information about the decision-making style might be an indicator of enlistment behavior.…”
Section: Knowledge Of Military Factssupporting
confidence: 78%
“…Our interviews with individuals in the DEP conducted in the first phase of the project (Sticha et al, 1997) indicated that some did not have definite plans for their lives before they enlisted. This result was similar to a decision making style that was identified by in depth follow-up interviews conducted with YATS respondents (Berkowitz, Perry, Giambo, Wilson, & Lehnus, 1997). These results suggested that information about the decision-making style might be an indicator of enlistment behavior.…”
Section: Knowledge Of Military Factssupporting
confidence: 78%
“…In addition, each percentage point increase in the enlistment rate by zip code was also associated with being 380 times more likely to join the military (Ford et al, 2014). A study of military propensity of young women suggested that women who join typically have a clear set of education goals and career aspirations and are familiar with the military, either through participation in Junior Reserve Officers' Training Corps or by growing up in a family with strong military traditions (Berkowitz, Achatz, and Westat, 1999).…”
Section: Propensity For Military Servicementioning
confidence: 99%